Improving Innovative Work Behavior Through Creative Self Efficacy And Transformational Leadership - Hutagalung, Mery Togi Parsaulian; Liestiawati, Fibria Indriati Dwi (UNIVERSITAS PAKUAN, 2024)
Innovation is important for organizations to survive and thrive. Therefore, innovative work behavior is demanded of employees at work. To enhance innovative behavior, it needs to be supported by several factors including leadership style and employee confidence in carrying out their duties. This article aims to provide an overview of the role of transformational leadership and creative self-efficacy in developing innovative work behavior in public organizations. Another aims of this literature review is to provide an overview of the challenges faced in implementing transformational leadership and creative self-efficacy to foster innovative work behavior in public organizations. This article was created through a review of the literature, taken from various journals that have been published nationally and internationally, conference papers, and books. The results obtained from various previous studies show that creative self-efficacy and transformational leadership are key factors in encouraging innovative work behavior among staff members in public organization. And when applying transformational leadership and creative self-efficacy in the public sector faces various challenges that come from various factors including individual factors. To overcome these challenges, this study recommends the application of transformational leadership, which emphasizes inspiring and empowering employees to think creatively and contribute to organizational innovation efforts.